FAM19A1, a brain‐enriched and metabolically responsive neurokine, regulates food intake patterns and mouse behaviors. Issue 12 (5th November 2019) - Lei, Xia; Liu, Lili; Terrillion, Chantelle E.; Karuppagounder, Senthilkumar S.; Cisternas, Pedro; Lay, Mark; Martinelli, David C.; Aja, Susan; Dong, Xinzhong; Pletnikov, Mikhail V.; Wong, G. William
Abstract : Cytokines and chemokines play diverse roles in different organ systems. Family with sequence similarity 19, member A1‐5 (FAM19A1‐A5; also known as TAFA1‐5) is a group of conserved chemokine‐like proteins enriched in the CNS of mice and humans. Their functions are only beginning to emerge. Here, we show that the expression of Fam19a1‐a5 in different mouse brain regions are induced or suppressed by unfed and refed states. The striking nutritional regulation of Fam19a family members in the brain suggests a potential central role in regulating metabolism. Using a knockout (KO) mouse model, we show that loss of FAM19A1 results in sexually dimorphic phenotypes. In male mice, FAM19A1 deficiency alters food intake patterns during the light and dark cycle. Fam19a1 KO mice are hyperactive, and locomotor hyperactivity is more pronounced in female KO mice. Behavior tests indicate that Fam19a1 KO female mice have reduced anxiety and sensitivity to pain. Spatial learning and exploration, however, is preserved in Fam19a1 KO mice. Altered behaviors are associated with elevated norepinephrine and dopamine turnover in the striatum. Our results establish an in vivo function of FAM19A1 and highlight central roles for this family of neurokines in modulating animal physiology and behavior.—Lei, X., Liu, L., Terrillion, C. E., Karuppagounder, S. S., Cisternas, P., Lay, M., Martinelli, D. C., Aja, S., Dong, X., Pletnikov, M. V., Wong, G. W. FAM19A1, a brain‐enriched and metabolically responsive neurokine, regulates food intake patterns and mouse behaviors. FASEB J. 33, 14734‐14747 (2019). www.fasebj.org